TRANSFORMATION OF THE EDUCATIONAL PROCESS IN THE MODERN INFORMATION SPACE - E. V. Pirainen (Дискурс)
The phenomenon of «clip-thinking» and its influence on the education process is described in the article. The problems of the classical model of education are shown. Methods of classical education are aimed at logical thinking, but peculiarities of perception of the modern generation have a significant impact on the effectiveness of the education process. In examples of transformation of the educational process are given the article and a number of issues caused by these changes are identified as well as possible solutions of these problems.